Methods of defining hypertension in electronic medical records: validation against national survey data - Mingkai Peng; Guanmin Chen; Gilaad Kaplan; Lisa Lix; Neil Drummond; Kelsey Lucyk; Stephanie Garies; Mark Lowerison; Samuel Weibe; Hude Quan (International Journal of Population Data Science, 2017)
ABSTRACT